GranDIHC-BR 2025-2035 - GC7: Interaction with Emerging Technologies: An Ecosystem Integrating Humans, Technologies, and Contexts - Zaina, Luciana; Prates, Raquel Oliveira; Delabrida Silva, Saul Emanuel; Choma, Joelma; Valentim, Natasha Malveira Costa; Frigo, Luciana Bolan; Bicho, Alessandro de Lima (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
This article discusses the grand challenge of Emerging Technologies, which is part of the seven Grand Challenges of the Human-Computer Interaction (HCI) community for the years 2025-2035 in Brazil. Emerging technologies are characterized by significant scientific advances and rapid adoption, such as the Internet of Things (IoT), 5G, Big Data, Analytics, Artificial Intelligence (AI), Robotics, and Virtual/Augmented/Mixed Reality (VR/AR/MR). Alongside the development of these technologies, various applications are emerging from a symbiosis among individuals, technologies, and contexts that make up a complex ecosystem. The emerging use of these technologies by human beings reveals specific demands for interaction in this ecosystem, highlighting the relevance of this topic. From an HCI perspective, this article discusses how the Brazilian scientific community should contribute over the next decade to effectively adopt emerging technologies and/or the emerging use of technologies in different contexts. Throughout the text, the identified issues pertinent to this challenge are analyzed from the perspective of how the elements of the ecosystem interact, contextualizing them at a national and global level. An agenda of six research topics is presented, actions to overcome the challenge are discussed, and the expected results for each are listed. Finally, ethical issues regarding research with emerging technologies are highlighted, and a final discussion regarding the other six challenges that are part of the HCI Grand Challenges is presented.